Social Dynamics and Community Identity Change Among the Residents Around UIN Sunan Ampel Surabaya - Rizka Dwi Nurhana; Aditya Hermansyah (Journal of Social Studies Education and Humanities Research, 2024)
The State Islamic University of Sunan Ampel Surabaya (UINSA), previously known as the State Institute of Islamic Studies (IAIN) Sunan Ampel, has undergone significant changes since its establishment in 1965, culminating in its transformation into UINSA in 2013. UINSA introduced the "twin towers" concept as a multidisciplinary scholarly development model integrating religious sciences with social sciences and natural sciences. This study employs a qualitative method with a descriptive approach to describe the social dynamics before and after the establishment of the twin towers at UINSA. Data were obtained through literature studies and interviews with academic staff and administrative personnel. The research was conducted around the Twin Towers on March 19, 2024. The findings indicate that the construction of the Twin Towers has triggered significant social changes in several aspects: technology and infrastructure, economy and commercial activities, culture and social interactions, as well as politics and policy. Additionally, the community identity around the Twin Towers has undergone transformation, including changes in collective identity, socialization processes, and the influence of external and internal factors. Conflict theory, symbolic interactionism, structuration theory, and social change theory were used to analyze these dynamics. These changes have created a more modern and globally connected environment, but also bring challenges in resource management and social integration.